Metabolic syndrome and its predictors among adults seeking medical care: A trending public health concern. (April 2023) - Jemal, Awol; Girum, Tadele; Kedir, Shemsu; Bedru, Abdurehim; Mosa, Hassen; Assfa, Kenzudin; Oumer, Abdu
Summary: Background: Metabolic syndrome (Mets) is a cluster of cardiovascular risk factors secondary to an inflammatory and insulin resistance state that increases the risk of cardiovascular disease and type 2 diabetes mellitus. However, there is limited evidence on it despite an increasing metabolic syndrome (Mets) related morbidity and mortality. Objective: This study was to identify the magnitude and factors associated with Mets among adults seeking care in Southern Ethiopia. Method: An institution-based cross-sectional study design was conducted on randomly selected 361 adults through face-to-face interviews and biomarker assessments. Mets were defined according to the NECP/ATP III criteria which are based on biochemical and lifestyle indicators. Bivariable and multivariable logistic regression analyses were used to identify factors associated with Mets. Crude and adjusted odds ratio with their 95% confidence interval was reported. Model fitness was checked using the Hosmer and Lemeshow tests. Multicollinearity diagnostic was checked using inflated standard error and variance inflation factor. Statistical significance was affirmed at a p -value <0.05. Results: A total of 351 respondents were studied, with a response rate of 97.2%. Overall, the magnitude of Mets among adults was 18.5% (95% CI: 14.4–22.6%). Individuals with BMI ≥25 kg/m 2 (AOR = 4.1; 95% CI = 3.13–11.51), having a sedentary behavior ≥8 h per day (AOR = 3.76; 95% CI = 1.38–10.25), adequate fruit or vegetable consumption (AOR = 0.48; 95% CI = 0.27–0.92), being involved in physical activity (AOR = 0.41; 95% CI: 0.20–0.80) and consuming alcohol 5–6 days per week (AOR = 2.9; 95% CI: 1.11–7.55) were significantly associated with Mets. Conclusion: the burden of Mets is a major public health concern among adults which is closely linked to physical activity, optimum body weight, fruit and vegetable consumption, and sedentary lifestyles.